The Implementation of Collaborative Strategy in Teaching Students Reading Comprehension at SMP Negeri 12 Palu - Siti Aisyah; Konder Manurung; Andi Patmasari; Aminah Aminah (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This research investigates the implementation of collaborative strategies in teaching reading comprehension to students at SMP Negeri 12 Palu. The study highlights the significance of reading as a fundamental skill that enhances knowledge and vocabulary. Despite its importance, many students struggle with reading comprehension due to factors such as lack of interest, limited vocabulary, and ineffective teaching methods. This research aims to apply collaborative reading strategies to improve students' comprehension skills. A pre-experimental design was utilized, involving a pretest and posttest to measure the effectiveness of the intervention. The results indicate a significant improvement in students' reading comprehension, suggesting that collaborative strategies foster better understanding and engagement in reading activities. The findings provide practical implications for teachers to enhance reading instruction and promote a more dynamic learning environment.